DIGITAL TEACHING COMPETENCE IN HIGHER EDUCATION. - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2021)
Higher education is one of the educational stages most affected by digital technologies, whose constant development has produced a favourable atmosphere for new approaches regarding the teaching–learning processes.